The effects of firm relocation on firm performance - A literature review - Joris Knoben; Leon Oerlemans (European Regional Science Association (ERSA), 2005)
Approximately 6% of all firms in the Netherlands decide to relocate every year. Furthermore, the number of firms that has relocated increased dramatically over time. Relatively much is known about the (re)location decision itself. However, much less research focuses on the effects of relocation on the performance of firms. This is remarkable since the importance of the geographical and organizational position of a firm for firm performance, and especially innovation, has become more and more profound over time. The notion that no firm may function as an island on itself is accepted by and large and the importance of a firm's geographical and organizational position is sometimes even described as exaggerated in the literature. It therefore seems logical to study the effects of changes in a firm's position as a result of a relocation. Given the above this paper asks the question: What is known in the literature about the effects of firm relocation on the performance of firms? In order to answer this question, first an overview of the possible effects of firm relocation is given. Subsequently, a review of the available literature dealing with the effects of firm relocation is presented in order to make an inventory of the effects that have and have not been studied. It is argued that the scarce relocation literature that is available has an extremely narrow focus and largely neglects the importance of the geographical and organizational position of a firm and thereby might ignore important factors influencing the effects of firm relocation on firm performance.
Keywords: 330